2021
DOI: 10.1002/trc2.12175
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid intake and incident dementia in the Danish Diet, Cancer, and Health cohort

Abstract: Introduction Prospective studies investigating flavonoid intake and dementia risk are scarce. The aims of this study were to examine associations between flavonoid intake and the risk of incident dementia and to investigate whether this association differs in the presence of lifestyle risk factors for dementia. Methods We examined associations in 55,985 participants of the Danish Diet, Cancer, and Health Study followed for 23 years. The Phenol‐Explorer database was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…There is more evidence for a protective role of flavonoids in the development of neurological diseases [ 41 ] with mechanisms including a reduction in reactive oxygen species and amyloid beta-protein production [ 42 ]. Recent data also suggest that higher intake of flavonoids and flavonoid-rich foods are associated with a lower risk of Alzheimer’s, dementia, and Parkinson’s disease [ 43 46 ] but our data are the first to suggest that increasing intakes in mid-life can reduce risk of neurological death. Although we include a lag time of 2 years, we cannot discount the possibility that observed associations may be attributed to reverse causation, in particular, that a higher risk of neurological death may be linked to a decrease in intakes of flavonoid-rich foods.…”
Section: Discussionmentioning
confidence: 51%
“…There is more evidence for a protective role of flavonoids in the development of neurological diseases [ 41 ] with mechanisms including a reduction in reactive oxygen species and amyloid beta-protein production [ 42 ]. Recent data also suggest that higher intake of flavonoids and flavonoid-rich foods are associated with a lower risk of Alzheimer’s, dementia, and Parkinson’s disease [ 43 46 ] but our data are the first to suggest that increasing intakes in mid-life can reduce risk of neurological death. Although we include a lag time of 2 years, we cannot discount the possibility that observed associations may be attributed to reverse causation, in particular, that a higher risk of neurological death may be linked to a decrease in intakes of flavonoid-rich foods.…”
Section: Discussionmentioning
confidence: 51%
“…The primary aim of this study was to investigate the associations between intakes of 1) total flavonoids, 2) flavonoid subclasses and 3) key flavonoid compounds within respective subclasses with incident COPD in the Danish Diet, Cancer and Health cohort. In our previous work, a consistent finding was that associations between flavonoid intake and a range of chronic diseases (including cardiovascular disease, dementia and diabetes [ 15 , 16 ]) were stronger in current and former smokers. Given the importance of smoking as a risk factor for COPD, the purported antioxidant and anti-inflammatory properties of flavonoids, and that there is evidence of sex-related differences in COPD risk and outcomes [ 17 ], secondary aims were to explore interactions between flavonoid intakes and risk factors for COPD, namely sex and smoking.…”
Section: Introductionmentioning
confidence: 71%
“…A total of 1823 studies were identified through the search strategy ( Figure 1 ). Out of these, after examination of the title ( n = 1303) and abstract ( n = 521) and full texts ( n = 487), 37 articles [ 15–51 ] were included in this review. The main characteristics of the included studies are presented in Table S2, Supporting Information.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this association was stronger in smokers (Q3 vs Q1 of flavanones, HR = 0.89, 95% CI: 0.80, 0.99) and significant for vascular dementia (Q3 vs Q1 of flavonols, HR 0.64, 95% CI: 0.48, 0.84), but no association was observed for Alzheimer's disease or unspecified dementia risk. [ 49 ] In a prospective study of 1329 participants of the Three Cities (3C) Bordeaux Cohort with a 12‐year follow‐up, authors analyzed different patterns of (poly)phenol consumption in association with risk of Alzheimer: compared to lowest exposure, individuals in the highest quintile of a high‐(poly)phenol pattern score had 50% lower probability of developing dementia (HR = 0.50, 95% CI: 0.32, 0.80) and 48% lower risk of Alzheimer's disease (HR = 0.52, 95% CI: 0.29, 0.93). [ 50 ] Finally, in a recent report from the JPHC including 8991 men and 22 456 women followed for an average of 9.4 years, the incidence risk of disabling dementia (defined as dementia that required care) was unrelated to intake of isoflavones in both men and women (Q5 vs Q1, HR = 1.05, 95% CI: 0.90, 1.24 and HR = 0.98, 95% CI: 0.86, 1.12, respectively).…”
Section: Resultsmentioning
confidence: 99%